Medical remotely caring with COVID-19 virus infected people using optimized wireless arm tracing system - Mohammed Azher Therib; Ahmed Fahem Al-Baghdadi; Heyam Marzog (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A human arm makes many functions that a robotic arm always programmed to make same functions. The human limbs motion can be captured using sensors that they will always copy hand movement. The rapid spread of the Coronavirus (COVID-19) virus and contacting the infections make the number of patients doubled in short time. The system proposed in this research can protect clinicians against infection with virus by reducing the contact with the infected and treat them remotely. This system type can be useful in different other fields of industrial works and defense where dangerous and delicate task can be done remotely without actual touch. Xbee shield is used to allow a hand glove flex sensor to communicate with the robotic arm using Zigbee wirelessly. Zigbee here is based on Xbee module from Max stream that can be communicate outdoor for 300 feet with the line of sight and indoor for 100 feet. Proportional, integral and derivative (PID) controller used in the proposed system to achieve smooth movement of limbs. The desired signal comes from flex sensor that connected to each limb. Kalman estimator proposed to find current state of each limb. In order to get better performance, particle swarm optimization (PSO) is used.